Estudio de seguridad vial para determinar la incidencia del diseño geométrico en la accidentalidad carretera Bogotá-Villavicencio a partir de la salida del túnel de Boquerón a puente Quetame (2014)
Road accidents are one of the main causes of death of people, that is why the road safety that has a road is of great importance, because if this is inadequate can lead to a high rate of accidents with killed and wounded, not only in motorized or non-motorized vehicles, but also includes vulnerable users who drive on a road. Improving road safety on highways is one of the main concerns with which it is counted in the different countries. Considering that road accidents are the second cause of death worldwide, it is considered important to review the projects from the geometric design stage to the start-up, for the improvement of the infrastructure both in terms of problems manifest in high occurrences of accidents, such as to sites with deficiencies in which there is no manifestation of accidents at any given time; but which could potentially lead to high incidences (preventive approach). The present study shows the relationship between the accident rate and the geometric design of the Bogotá-Villavicencio road from the section between the exit of the Boquerón tunnel to the Puente Quetame toll, in stage of operation and in design, for this purpose, checklists were implemented in the consideration of the geometric design parameters of the INVIAS 2008 Design Manual and the preventive safety factors for roads, which is compatible with the approach currently applied in the road safety audits, which seek to detect critical points of road accident. The road infrastructure is one of the accident factors with 28%. This is why the consistency in the design of a road is related to the conformity of its geometry and road safety.